Pemberhentian Ketua Mahkamah Konstitusi Tidak Dengan Hormat Dalam Lembaga Mahkama Konstitusi - Rawulunubun, Ignasius; Baranyanan, Soeleman Djaiz (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2025)
The dismissal of constitutional judges whose term of office has not yet expired must refer to Law Number 7 of 2020 concerning the Constitutional Court, specifically Article 23, therefore the dismissal of constitutional judges that do not refer to the Constitutional Court Law is declared unconstitutional because it is contrary to the 1945 Constitution of the Republic of Indonesia Article 24C paragraph (6) and Article 25 dismissing the Chief Justice of the Constitutional Court Anwar Usman by the Constitutional Court Honorary Council (MKMK) in Decision Number 02/MKMK/L/11/2023, is suspected of violating the Code of Ethics and Guidelines for the Conduct of Constitutional Judges. The alleged violation is based on the involvement of the Chief Justice of the Constitutional Court Anwar Usman in case Number 90/PUU-XXI/2023 which was intended to pave the way for the Mayor of Solo Gibran Rakabuming Raka who is the nephew of the Reported Judge and the son of President Joko Widodo to meet the qualifications to compete as a Presidential candidate or Vice Presidential candidate in the 2024 Simultaneous General Election. In the involvement of the reported judge, Anwar Usman is considered to have violated the Basic Principle of Justice, namely impartiality. However, the dishonorable dismissal sanction read out by the Chairman of the Constitutional Court's Honorary Council in Decision Number 02/MKMK/L/11/2023, does not comply with the sanctions contained in Article 23 of Law Number 7 of 2020 concerning the Third Amendment to Law Number 24 of 2003 concerning the Constitutional Court and Article 41C in conjunction with 47 of the Constitutional Court Regulation Number 1 of 2023 concerning the Constitutional Court's Honorary Council.